Analysis of the relationship between modernity and economic development Analysis of the relationship between modernity and economic development - صالح, لورنس يحيى; جناني, حامد رحيم (Journal of Economics and Administrative Sciences, 2017)
This research shows the problem of the economic development of underdeveloped countries in an unconventional way, as these papers explain the problems of the economic development. This research not only reviews the problems, but it illustrates them in a philosophical way, basis of the data of modernity, this mean it is a process of connecting between the absence of the modernity values and the failure of development in underdeveloped countries. The Search follows the descriptive approach to get to the goal of search by four main axes. The first axis includes clarifying  modernity and its principles, the second axis includes clarifying the economic development , the third axis includes the features of the modern state and its relationship with the economic development of the underdeveloped countries and the fourth axis clarify underdeveloped countries and the absence of modern thought.The research found that the absence of modern thought is an obstacle facing the underdeveloped countries  .